Strategi Komunikasi Pemasaran Hotel dalam Meningkatkan Angka Okupansi: Studi Kasus Hotel Yasmin Karawaci Pasca pandemi Covid-19 - Tasyharani, Alfiandi; Furkon, Ukon; Mirza, Mochammad (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
Life after the Covid-19 pandemic has started since the middle of 2022. The impact of the Covid-19 pandemic has brought losses to business people, one of which is hotel services, which can be said to be the first to be affected by the Covid-19 pandemic and experience delays in recovering it. This research aims to find out the marketing communication strategy carried out by Hotel Yasmin Karawaci in increasing the occupancy rate after the Covid-19 pandemic. Having been used as a quarantine place for Covid-19 isolation patients for 2 years, the Yasmin Karawaci Hotel had to rise again to increase hotel occupancy rates and convince guests and potential guests that the hotel was free from the spread of Covid-19. To explain this situation, researchers use qualitative methods. The results obtained are that Yasmin Karawaci Hotel has carried out a good and effective marketing communication strategy in increasing hotel occupancy rates which refers to the "marketing communication mix". By implementing this strategy to attract guests and potential guests who want to stay at the hotel, it is evident that the number of guests has increased gradually. To overcome the obstacles experienced in implementing the post-pandemic Covid-19 marketing communication strategy, Hotel Yasmin Karawaci always conducts evaluations with hotel staff and employees.